LISTENING COMPREHENSION: THE IMPACT OF SUBTITLES TYPOGRAPHICAL FEATURES ON GAME VISUAL NOVEL - Kusumawati, Eny (Faculty of Letters, Dr. Soetomo University, 2019)
The purpose goal of this study was to test the impact of typographical features of subtitles including size, colour and position on L2 English viewers? retention and recall of texts in game visual novel, and also the voice effect of the visual game. Quasi experimental research played in this study with 54 students of two departments, with the same characteristics. It was played the game visual novel into both classes, and administered 45 multiple choice test and questioners in the end of the classes. Both classes went through the same procedures, but one class watched the customized subtitled of the visual game novel. The data gathered were subjected to the statistical procedure of paired sample t-test. And, the result showed that the experimental class showed the better result on their understanding of the story, but there is contrarily on their listening comprehension result, that is their vocabulary comprehension, it is found that the both subtitles did not have an effect on participants? comprehension. This study has implications for English language teachers and material developers to benefit customized bimodal subtitles as a mnemonic tool for better comprehension, retention and recall of aural content in game visual novel via Computer Assisted Language Teaching approach. Keywords: Typographical features, game visual novel, subtitles, retention and recall, Listening, vocabulary comprehension.